2013
DOI: 10.1111/are.12235
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for spawning and growth traits in the Pacific white shrimp (Penaeus (Litopenaeus) vannamei)

Abstract: The aim of this study was to estimate genetic parameters for spawning traits and growth traits in a breeding line of Pacific white shrimp, Penaeus (Litopenaeus) vannamei, selected for growth and survival. Traits studied were number of eggs (NE) and number of nauplii (NN) and female body weight at insemination (FWI) and body weight at 130 days of age (BW130). Genetic parameters were estimated using a multivariate animal model. Heritability for NE and NN were estimated as 0.13 ± 0.04 and 0.03 ± 0.04 respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
(60 reference statements)
5
10
1
Order By: Relevance
“…While we observed this effect in our study (Ren et al, in press), positive correlations between body size of broodstock and spawning frequency have also been reported previously in a variety of farmed penaeid species 35,36 . The mean number of eggs per spawn (NE) reported here (225.15 × 10 3 ) was consistent with the estimates reported in two other studies on reproductive traits in female P. vannamei in Mexico 26,27 (mean = 217.90 × 10 3 ; 216.0 × 10 3 ), and higher than the values (160.7 × 10 3 ) reported by Tan, et al 28 . The estimates of nauplii per spawn (NN) and hatching rate of eggs (HR) in our study were similar to the estimates reported by Arcos et al 26 (NN = 187.8 × 10 3 , HR = 86.20%), but significantly higher than that reported by Caballero-Zamora et al 27 (NN = 47.0 × 10 3 , HR = 21.76%) and Tan et al 28 (NN = 34.7 × 10 3 , HR = 21.59%), respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While we observed this effect in our study (Ren et al, in press), positive correlations between body size of broodstock and spawning frequency have also been reported previously in a variety of farmed penaeid species 35,36 . The mean number of eggs per spawn (NE) reported here (225.15 × 10 3 ) was consistent with the estimates reported in two other studies on reproductive traits in female P. vannamei in Mexico 26,27 (mean = 217.90 × 10 3 ; 216.0 × 10 3 ), and higher than the values (160.7 × 10 3 ) reported by Tan, et al 28 . The estimates of nauplii per spawn (NN) and hatching rate of eggs (HR) in our study were similar to the estimates reported by Arcos et al 26 (NN = 187.8 × 10 3 , HR = 86.20%), but significantly higher than that reported by Caballero-Zamora et al 27 (NN = 47.0 × 10 3 , HR = 21.76%) and Tan et al 28 (NN = 34.7 × 10 3 , HR = 21.59%), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Reproductive traits in farmed penaeid species (specifically fecundity-related traits), are among those that can contribute the most to increasing profitability of the hatchery sector but to date, only a single study has reported h 2 estimates for the above traits under commercial hatchery conditions 26 . While there have been two studies estimating genetic parameters for reproductive traits in Pacific white shrimp (P. vannamei) following artificial insemination 27,28 , more information will be required for the seed production sector because these studies indicate that there are differences in reproductive trait data when applying artificial insemination vs natural mating in penaeid species. Moreover, high levels of additive genetic variance in reproductive traits for mean oocyte number, diameter, ovary maturity stage 29 , and high genetic correlations between levels of vitellogenin in haemolymph and mean diameter of oocytes have been reported for Pacific white shrimp 30 .…”
mentioning
confidence: 99%
“…Due to incomplete data recording of reproductive traits and the small genetic variances, genetic correlations of female weight with fecundity, total zoea weight and PL first age were not estimable. In White leg shrimp, genetic correlations of female weight with fecundity or fry weight estimated were positive, but all the estimates were associated with high standard errors (Caballero‐Zamora et al., ). Further study is needed to better understand genetic relationship between growth and the traits measured here.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic parameters for reproductive traits are generally dispersed in prawn/shrimp species. Earlier studies reported low to moderate heritability for days to spawn, egg/or nauplii number and hatching rate in tiger prawn Penaeus monodon (Macbeth et al., ) or egg/oocyte diameter, measures of egg quality and vitellogenin in haemolymph (Arcos, Racotta, & Ibarra, ; Ibarra, Famula, & Arcos, ) and spawning related traits in White leg shrimp Liptopenaeus vannamei (Caballero‐Zamora et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, 20 shrimp hatcheries generate 10 billion postlarvae annually through genetic selection programs (Mendoza-Cano, Enríquez-Espinoza, Encinas-García, & Sánchez-Paz, 2014) with both genetic traits. The development of faster growth lines has been carried out according to body weight and growth for increasing the genetic gain for growth at harvesting age (Caballero-Zamora et al, 2015;Campos-Montes, Montaldo, Martínez-Ortega, Jiménez, & Castillo-Juárez, 2013;Castillo-Juárez, Montaldo, & Campos-Montes, 2010).…”
Section: Introductionmentioning
confidence: 99%